Contextual teaching learnıng in human digestive system: The contribution of critical thinking skills - Yakobus Bustami; L Leliavia; Nyeria Elisabeth; Adriana Gandasari; Desi Ratnasari (Universitas Negeri Jakarta, 2020)
Critical thinking skills and students' understanding are the supporting factors in students’ learning success. This research aimed to determine the contrıbutıon of critical thinking skills for the understanding on human digestive system concepts when contextual teaching and learning (CTL) was implemented. The samples were 45 students consisting of public junior high schools 2 and 5 class VIII A at Sungai Tebelian. The instrument of critical thinking skills were essay test totaling of 6 items and to measure the understanding on human digestive system concepts, 20 items of multiple choices test were used. Research data were analyzed using a simple regression correlation analysis. The results showed a significant correlation of critical thinking skills to the understanding of human digestive system concepts. The regression equation of the correlation between the two variables was Y = 0.736X + 22.861. The correlation coefficient was 0.640, with the contribution the critical thinking skills to human digestive system concepts of 41.00%. These results showed that there was a significant correlation between critical thinking skills and human digestive system concepts when CTL was implemented in learning. Thus, biology teachers need to develop students’ critical thinking skills through the implementation of CTL in learning.